Aberrant Expression of ADARB1 Facilitates Temozolomide Chemoresistance and Immune Infiltration in Glioblastoma - Lu, Can; Chen, Xi; Yan, Yuanliang; Ren, Xinxin; Wang, Xiang; Peng, Bi; Cai, Yuan; Liang, Qiuju; Xu, Zhijie; Peng, Jinwu (Frontiers in Pharmacology, 2022)
Chemoresistance, especially temozolomide (TMZ) resistance, is a major clinical challenge to the treatment of glioblastoma (GBM). Exploring the mechanisms of TMZ resistance could help us to identify more effective therapies. Adenosine deaminase acting on RNA (ADARs) is very important in the process of RNA modification through regulating the A-to-I RNA editing. Recent studies suggest that ADARs regulates a variety of neurotransmitter receptors, which is closely related to the occurrence and progress of GBM. Here, the data from several bioinformatics databases demonstrated that adenosine deaminase RNA specific b1 (ADARB1), also named ADAR2, was obviously upregulated in both GBM tissues and cells, and has the prognostic value in GBM patients. Moreover, ADARB1 was found to be involved in AKT-mediated TMZ resistance of GBM cells. The KEGG analysis of ADARB1 associated co-expression genes showed that ADARB1 was potentially involved in the process of mitochondrial respiratory chain complex. TISIDB and GEPIA databases were further used to analyze the role of ADARB1 in tumor-immune system interactions in GBM. These findings deepened our comprehension of the function of ADARB1 in tumorigenesis and therapeutic response of GBM.